Evolution of Type D Personality Traits After Cochlear Implantation in Severely Hearing Impaired Adults 55 Years and Older: An Exploratory Prospective, Longitudinal, Controlled, Multicenter Study. Issue 8 (September 2022) - Andries, Ellen; Bieńkowska, Katarzyna; Świerniak, Weronika; Skarżyński, Piotr Henryk; Skarżyński, Henryk; Calvino, Miryam; Cuadrado, Isabel Sanchez; Muñoz, Elena; Gavilán, Javier; Lassaletta, Luis; Tavora-Vieira, Dayse; Acharya, Aanand; et al.
Abstract : Purpose: To study the evolution of type D personality traits in older adults after cochlear implantation compared with a control group of severely hearing impaired older adults who did not receive a cochlear implant (CI). The influence of COVID-19 on this evolution was also explored. Type D personality combines a high degree of negative affectivity (NA) and social inhibition (SI). Methods: In this prospective, longitudinal, controlled multicenter exploratory study, 76 older CI users and 21 severely hearing impaired controls without CI were included. The CI group and the control group did not differ significantly regarding age, formal education, residual hearing, Type D Scale-14 (DS14) total score, NA, and SI at baseline. Type D personality traits were assessed with the DS14 at baseline (T0) and 14 months later (T14). Results: Type D personality traits differed significantly over time between the CI group and the control group ( p < 0.001). In the CI group, the DS14 total score (mean delta T = −6.63; p < 0.001), NA (mean delta T = −3.26; p < 0.001), and SI (mean delta T = −3.37; p < 0.001) improved significantly over time (delta T = T14–T0), whereas no significant difference was found in the control group. Significantly fewer subjects were categorized as type D personalities in the CI group (delta T = −12; p = 0.023) at T14, whereas no significant change was found in the control group (delta T = 3; p = 0.250). COVID-19 did not influence the evolution of type D personality traits significantly in the CI group. Conclusion: Cochlear implantation has a positive effect on type D personality traits in older adults with a severe-to-profound hearing impairment.